The Liberating Transformation of Jesus from Greek-Roman Imperialism - Yosa Marianta Hetharie (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
This paper offers a postcolonial feminist reading of John 7:53-8:11, which focuses on the imperialistic background behind the text. The issue is that the violence experienced by the women in the text is not solely influenced by patriarchal culture. The aim of this paper is to analyze the background of the text more deeply, particularly the influence of the Roman Empire during that time. The method used is the postcolonial feminist hermeneutics developed by Musa W. Dube. The new perspective offered is that women are not deserving of violence, neither by culture nor by the binding imperial system.